Communication: Fundamental measure theory for hard disks: Fluid and solid - Roth, Roland; Mecke, Klaus; Oettel, Martin (Journal of Chemical Physics, 2012)
Two-dimensional hard-particle systems are rather easy to simulate but surprisingly difficult to treat by theory. Despite their importance from both theoretical and experimental points of view, theoretical approaches are usually qualitative or at best semi-quantitative. Here, we present a density functional theory based on the ideas of fundamental measure theory for two-dimensional hard-disk mixtures, which allows for the first time an accurate description of the structure of the dense fluid and the equation of state for the solid phase within the framework of density functional theory. The properties of the solid phase are obtained by freely minimizing the functional. (C) 2012 American Institute of Physics. [http://dx.doi.org/10.1063/1.3687921]
Keywords: density functional theory; equations of state